Pseudopollen in Camellia oleifera and its implications for pollination ecology and taxonomy - Yuan, Bin; Yuan, Jing-Kun; Huang, Cheng-Gong; Lian, Jia-Rui; Li, Yi-Huan; Fan, Xiao-Ming; Yuan, De-Yi (Frontiers in Plant Science, 2022)
Background and aims In 1997, Tsou described the special differentiation of the connective tissues of some species of Theaceae to produce single-celled powders with unique patterns called pseudopollen. The purpose of this study was to investigate the morphological structure of the pseudopollen of Camellia oleifera (Theaceae) and to study the morphology of pseudopollen in seven other Camellia species. Methods Scanning electron microscopy, paraffin section, light microscopy, transmission electron microscopy, histochemistry. Key result C. oleifera pseudopollen was similar to normal pollen in macroscopic morphology but different microscopically. The normal pollen was starch-rich and yellow, with mostly reticulate exine ornamentation. In contrast, the pseudopollen was a white powder, single-celled and rich in protein, with parallel unbranched ridge lines on the outer wall, and originated from the parenchyma of the connective tissues. There are also differences in the micro-characteristics of normal and pseudopollen among different species in Camellia. Conclusion There are great differences in morphological structure between C. oleifera and other species in Camellia normal pollen and pseudopollen; these results may indicate that the pseudopollen can be used as a taxonomic basis for Camellia, and the macroscopic similarity between pseudopollen and pollen and histochemical characteristics of pseudopollen can be a pollination strategy.